Respuesta :
I. f(2) when f(x) = 3x + 2
f(2) = 3(2) + 2=8
III. 2y + 14 = 4y − 2
4y- 2y = 14+2
2y = 16
y=16/2=8
statements have the same result
f(2) = 3(2) + 2=8
III. 2y + 14 = 4y − 2
4y- 2y = 14+2
2y = 16
y=16/2=8
statements have the same result
Answer:
All three statements have same results.
Step-by-step explanation:
Statement I: f(2) when f(x) = 3x + 2.
[tex]f(x)=3x+2[/tex]
Put x=2.
[tex]f(x)=3(2)+2=8[/tex]
The value of the function is 8. It means y=8 at x=2.
Statement II:f⁻¹(3). when f(x) = 2 x minus 7, all over 3.
[tex]f(x)=\frac{2x-7}{3}[/tex]
Find the inverse of the function.
Step 1: Substitute f(x)=y
[tex]y=\frac{2x-7}{3}[/tex]
Step 2: Interchange x and y.
[tex]x=\frac{2y-7}{3}[/tex]
Step 3: Isolate y.
[tex]y=\frac{3x+7}{2}[/tex]
Step 4: Substitute y=f⁻¹(x).
[tex]f^{-1}(x)=\frac{3x+7}{2}[/tex]
Now, substitute x=3, to find f⁻¹(3).
[tex]f^{-1}(3)=\frac{3(3)+7}{2}=8[/tex]
The result of statement II is 8.
Statement III: 2y + 14 = 4y − 2
[tex]2y+14=4y-2[/tex]
[tex]14+2=4y-2y[/tex]
[tex]16=2y[/tex]
[tex]y=8[/tex]
The result of statement III is 8.
Therefore all three statements have same results.